2022
DOI: 10.1001/jamaoto.2022.0848
|View full text |Cite
|
Sign up to set email alerts
|

Airway Complications Resulting From Pediatric Esophageal Button Battery Impaction

Abstract: IMPORTANCE Button batteries (BBs) are commonly found in many household items and present a risk of severe injury to children if ingested. The direct apposition of the trachea and recurrent laryngeal nerves with the esophagus puts children at risk of airway injury secondary to the liquefactive necrotic effects of BB impactions.OBJECTIVE To review airway injuries, including long-term sequelae, after BB ingestion in children.EVIDENCE REVIEW For this systematic review, a comprehensive strategy was designed to sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Philteos et al have clearly demonstrated the potential for airway injury from BB ingestion. Depending on the institution, esophageal BB cases may be primarily managed by otolaryngology, surgery, or gastroenterology services; a multidisciplinary team approach is important to ensure that a complete evaluation of the airway is performed.…”
Section: Current Statementioning
confidence: 99%
See 3 more Smart Citations
“…Philteos et al have clearly demonstrated the potential for airway injury from BB ingestion. Depending on the institution, esophageal BB cases may be primarily managed by otolaryngology, surgery, or gastroenterology services; a multidisciplinary team approach is important to ensure that a complete evaluation of the airway is performed.…”
Section: Current Statementioning
confidence: 99%
“…Ultimately, a new BB technology that reduces or eliminates severe tissue injury when BBs are lodged in the esophagus is critically needed . When a safer BB technology exists, industry should act quickly to adopt it; severe airway injuries and fatalities among children as described by Philteos et al may one day become obsolete.…”
Section: Role Of Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed diagnosis or recognition results in prolonged foreign body impaction time, which can lead to significant morbidity such as esophageal perforation, airway injury, and death. 1,[5][6][7] Identification of risk factors is a fundamental step in developing preventive strategies and decreasing morbidity and mortality in children.…”
Section: Introductionmentioning
confidence: 99%